RNA diversity has profound effects on the translation of neuronal nitric oxide synthase - Yang Wang; Derek C. Newton; G. Brett Robb; Cheng-Lin Kau; Tricia L. Miller; Anthony H. Cheung; Anne V. Hall; Suzannah VanDamme; Josiah N. Wilcox; Philip A. Marsden (1999)
A comprehensive analysis of the structure of neuronal nitric oxide synthase (nNOS; EC 1.14.13.39 ) mRNA species revealed NOS1 to be the most structurally diverse human gene described to date in terms of promoter usage. Nine unique exon 1 variants are variously used for transcript initiation in diverse tissues, and each is expressed from a unique 5′-flanking region. The dependence on unique genomic regions to control transcription initiation in a cell-specific fashion burdens the transcripts with complex 5′-mRNA leader sequences. Elaborate splicing patterns that involve alternatively spliced leader exons and exon skipping have been superimposed on this diversity. Highly structured nNOS mRNA 5′-untranslated regions, which have profound effects on translation both in vitro and in cells, contain cis RNA elements that modulate translational efficiency in response to changes in cellular phenotype.